THE EFFECT OF USING HIGH VOLUME FLY ASH (HVFA) ON THE PROPERTIES OF FRESH MORTAR - Puput Risdanareni, Tantri Raras Morowati (BANGUNAN, 2022)
Abstract: This study aims to understand the effect of using High Volume Fly Ash (HVFA) on the properties of fresh mortar. Mortar properties such as cement paste setting time, fresh mortar flow value, and mortar compressive strength were tested in this study. The results showed that the higher the fly ash content used in the mixture, the longer the paste setting time occurred. The initial bonding time of the cement paste with the control specimen, fly ash content of 0, 50 and 75% occurred at the 131st minute, 17.5th minute, 15th minute and 28th minute, respectively. The final binding time of the control sample cement paste, fly ash content of 0, 50 and 75% occurred in the 210th minute, 50th minute, 70th minute and 95th minute, respectively. The results showed that the use of High-Volume Fly Ash (HVFA) could increase the workability of fresh mortar. This is evidenced by the use of fly ash 50% causes an increase in flow value as much as 20.5% and the use of fly ash 75% causes an increase in flow value as much as 42.7%. Research proves that the higher the fly ash content used in the mixture, the lower the compressive strength value produced by the mortar. The results of the compressive strength test of HVFA mortar with control sample specimens, fly ash content of 0, 50 and 75% respectively were 16.6 Mpa, 6.3 Mpa, 5.2 Mpa, and 4.5 Mpa.Kata Kunci: HVFA, fresh mortar, setting time, compressive strength